1997
DOI: 10.1021/ma9612283
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Investigation of the Living Cationic Polymerization of Isobutylene Using a t-Bu-m-DCC/TiCl4/2,4-DMP Initiating System

Abstract: A kinetic and mechanistic study of the living cationic polymerization of isobutylene was conducted using 5-tert-butyl-1,3-bis(2-chloro-2-propyl)benzene (t-Bu-m-DCC)/TiCl4 initiating system with 2,4-dimethylpyridine (DMP) as an electron donor in 60/40 (v/v) hexane/methyl chloride cosolvents. The complex between TiCl4 and DMP was observed to be largely soluble in this medium in the temperature range −50 to −80 °C. Over the same temperature range using a [t-Bu-m-DCC]o:[TiCl4]o ratio of 1:20, polymerizations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(154 citation statements)
references
References 25 publications
14
137
3
Order By: Relevance
“…4 It seems reasonable that a similar reaction would occur in the formation of onium salts. If [TiCl 4 ] 0 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…4 It seems reasonable that a similar reaction would occur in the formation of onium salts. If [TiCl 4 ] 0 .…”
Section: Resultsmentioning
confidence: 98%
“…Under the most common reaction conditions, i.e., [TiCl 4 ] > the concentration of polymer chain ends (CE), a secondorder dependence on the [TiCl 4 ] has been consistently reported in a number of papers by at least two different groups. [3][4][5][6] The sole contrary report under these reaction conditions is that of Kennedy and co-workers, 19 who claimed a first-order [TiCl 4 ] dependence. A polymerization mechanism ( Figure 2) involving dimeric counterions of the type Ti 2 Cl 9 -has been advanced to account for the observed second-order dependency on [TiCl 4 ].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…All three methods yielded polymers with M -n A 400 000 g/mol. [24 -30] Kinetic investigations showed that living isobutylene polymerization co-initiated by TiCl 4 proceeds via ion pairs [19,31,32] and that the ionization equilibrium is strongly shifted towards covalent species (see Equation (6)). A similar mechanism was suggested for the living polymerization of isobutyl vinyl ether initiated by the monomer chloride/ZnCl 2 system.…”
Section: Living Carbocationic Polymerizationmentioning
confidence: 99%
“…[65] Fiber-optic real-time FTIR monitoring demonstrated that N,N-dimethylacetamide (DMA), a strong electron pair donor, complexes with TiCl 4 under polymerization conditions as postulated by Storey. [32] Figure 5 contains FTIR spectra of DMA before and after the addition of TiCl 4 . DMA has a strong carbonyl absorption at 1 659 cm -1 , and another strong band at 1 187 cm -1 , assigned to the amide groups.…”
Section: C) Kinetics and Mechanism Of Living Isobutylene Polymerizamentioning
confidence: 99%